Sex-specific effects of therapeutic hypothermia on short- and long-term microglial and astrocytic reactivity after severe neonatal hypoxia–ischemia - Ricardo Ribeiro Nunes; João Vitor Miotto Tauffer; Bianca Büchele Martins; Isadora D’Ávila Tassinari; Carlos Alexandre Netto; Ana Helena Paz; Luciano Stürmer de Fraga (Metabolic Brain Disease, 2026)

Regional Crosstalk Between the Amygdala, Hippocampus, and Prefrontal Cortex Following Na+,K+-ATPase Inhibition by Ouabain - Bianca Estefani Schmidt; Ana Karla Oliveira Leite; Clarissa Penha Farias; Alessandra Schmitt Rieder; Gustavo Ricardo Krupp Prauchner; Carlos Alexandre Netto; Angela T. S. Wyse (Neurotoxicity Research, 2026)
The Na⁺,K⁺-ATPase plays a fundamental role in memory formation by regulating neuronal excitability and NMDA receptor-dependent synaptic plasticity. While this enzyme’s dysfunction is broadly linked to cognitive disorders, its specific contribution to fear memory consolidation, particularly within the key brain structure of the basolateral amygdala (BLA), remains undefined. We investigate whether Na + ,K + -ATPase inhibition disrupts contextual fear conditioning (CFC) memory consolidation and examine downstream molecular, oxidative, and inflammatory responses in interconnected brain regions. Fifty-day-old male Wistar rats received bilateral cerebral infusions of the Na + ,K + -ATPase inhibitor ouabain (1 μm) or vehicle immediately after CFC training. Memory retention was assessed 24 h later. Additional cohorts were euthanized 6–24 h after infusion for biochemical analysis of Na + ,K + -ATPase activity, expression of Na + ,K + -ATPase isoforms (α1, α2, α3, β1), oxidative stress markers, and pro-inflammatory cytokines in the amygdala, hippocampus, and prefrontal cortex. Post-training Na + ,K + -ATPase inhibition in the BLA selectively impaired fear memory consolidation. Ouabain induced changes in Na⁺,K⁺-ATPase activity in the hippocampus and prefrontal cortex, and induces time-dependent upregulation of α1 and β1 isoforms. Six hours after infusion, ouabain triggered oxidative imbalance – characterized by reduced CAT activity. Pro-inflammatory cytokine expression was markedly elevated in the hippocampus and prefrontal cortex, while D-serine co-administration failed to rescue memory deficits. These findings establish a previously unrecognized role for Na⁺,K⁺-ATPase signaling in the BLA in coordinating the neurobiological processes essential for fear memory consolidation, indicating that its precise regulation is required for adaptive fear memory formation.

Differential effects of hypothermia and memantine in neonatal hypoxia-ischemia - Francielle Fernandes Spies; Ricardo Ribeiro Nunes; Isadora D’Avila Tassinari; Andrey Vinicios Soares Carvalho; Diorlon Nunes Machado; Rafael Bandeira Fabres; Carlos Alexandre Netto; Luciano Stürmer de Fraga (Metabolic Brain Disease, 2025)

Sex-Specific Differences in the Transport and Availability of Energy Substrates in the Hippocampus of Rats During Neurodevelopment - Kiara França Campos; Adriana Fernanda Kuckartz Vizuete; Diorlon Nunes Machado; Andrey Vinicios Soares Carvalho; Luz Elena Durán-Carabali; Carlos Alexandre Netto (Molecular Neurobiology, 2025)

Methylphenidate Exposing During Neurodevelopment Alters Amino Acid Profile, Astrocyte Marker and Glutamatergic Excitotoxicity in the Rat Striatum - Felipe Schmitz; Luz Elena Durán-Carabali; Alessandra Schmitt Rieder; Josiane S. Silveira; Osmar Vieira Ramires Junior; Larissa D. Bobermin; André Quincozes-Santos; Vinícius S. Alves; Robson Coutinho-Silva; Luiz Eduardo B. Savio; Daniella M. Coelho; Carmen R. Vargas; et al. (Neurotoxicity Research, 2024)

Bumetanide Attenuates Cognitive Deficits and Brain Damage in Rats Subjected to Hypoxia–Ischemia at Two Time Points of the Early Postnatal Period - Diorlon Nunes Machado; Luz Elena Durán-Carabali; Felipe Kawa Odorcyk; Andrey Vinicios Soares Carvalho; Ana Paula Rodrigues Martini; Livia Machado Schlemmer; Marcel de Medeiros de Mattos; Gabriel Pereira Bernd; Carla Dalmaz; Carlos Alexandre Netto (Neurotoxicity Research, 2023)

Serum of COVID-19 patients changes neuroinflammation and mitochondrial homeostasis markers in hippocampus of aged rats - Yorran Hardman A. Montenegro; Larissa Daniele Bobermin; Patrícia Sesterheim; Richard Steiner Salvato; Fernando Anschau; Maria José Santos de Oliveira; Angela T. S. Wyse; Carlos Alexandre Netto; Carlos-Alberto Saraiva Gonçalves; André Quincozes-Santos; Guilhian Leipnitz (Journal of NeuroVirology, 2023)

Glioprotective effects of resveratrol in hypothalamic astrocyte cultures obtained from interferon receptor knockout (IFNα/βR−/−) mice - Vanessa Sovrani; Larissa Daniele Bobermin; Patrícia Sesterheim; Ester Rezena; Matheus Sinhorelli Cioccari; Carlos Alexandre Netto; Carlos-Alberto Gonçalves; Guilhian Leipnitz; André Quincozes-Santos (In Vitro Cellular & Developmental Biology - Animal, 2023)

l-2-Hydroxyglutaric Acid Administration to Neonatal Rats Elicits Marked Neurochemical Alterations and Long-Term Neurobehavioral Disabilities Mediated by Oxidative Stress - Rafael Teixeira Ribeiro; Andrey Vinícios Soares Carvalho; Rafael Palavro; Luz Elena Durán-Carabali; Ângela Beatris Zemniaçak; Alexandre Umpierrez Amaral; Carlos Alexandre Netto; Moacir Wajner (Neurotoxicity Research, 2023)

A Review of In Silico Research, SARS-CoV-2, and Neurodegeneration: Focus on Papain-Like Protease - Alessandra S. Rieder; Bruna F. Deniz; Carlos Alexandre Netto; Angela T.S. Wyse (Neurotoxicity Research, 2022)

Therapeutic hypothermia for the treatment of neonatal hypoxia-ischemia: sex-dependent modulation of reactive astrogliosis - Rafael Bandeira Fabres; Ricardo Ribeiro Nunes; Marcel de Medeiros de Mattos; Mirella Kielek Galvan Andrade; Ana Paula Rodrigues Martini; Isadora D’Ávila Tassinari; Eduardo Farias Sanches; Luciano Stürmer de Fraga; Carlos Alexandre Netto (Metabolic Brain Disease, 2022)

Elusive deer occurrences at the Atlantic Forest: 20 years of surveys - Márcio Leite de Oliveira; Francisco Grotta-Netto; Pedro Henrique de Faria Peres; Alexandre Vogliotti; Carlos Rodrigo Brocardo; Jorge José Cherem; Mariana Landis; Roberta Montanheiro Paolino; Roberto Fusco-Costa; Andressa Gatti; Danielle Oliveira Moreira; Paula Modenesi Ferreira; et al. (Mammal Research, 2022)

Correction to: Stem Cells from Human Exfoliated Deciduous Teeth Modulate Early Astrocyte Response after Spinal Cord Contusion - Fabrício Nicola; Marília Rossato Marques; Felipe Odorcyk; Letícia Petenuzzo; Dirceu Aristimunha; Adriana Vizuete; Eduardo Farias Sanches; Daniela Pavulack Pereira; Natasha Maurmann; Carlos-Alberto Gonçalves; Patricia Pranke; Carlos Alexandre Netto (Molecular Neurobiology, 2019)

Stem Cells from Human Exfoliated Deciduous Teeth Modulate Early Astrocyte Response after Spinal Cord Contusion - Fabrício Nicola; Marília Rossato Marques; Felipe Odorcyk; Letícia Petenuzzo; Dirceu Aristimunha; Adriana Vizuete; Eduardo Farias Sanches; Daniela Pavulack Pereira; Natasha Maurmann; Carlos-Alberto Gonçalves; Patricia Pranke; Carlos Alexandre Netto (Molecular Neurobiology, 2019)

Synergistic Toxicity of the Neurometabolites Quinolinic Acid and Homocysteine in Cortical Neurons and Astrocytes: Implications in Alzheimer’s Disease - Paula Pierozan; Helena Biasibetti-Brendler; Felipe Schmitz; Fernanda Ferreira; Carlos Alexandre Netto; Angela T. S. Wyse (Neurotoxicity Research, 2018)

Vitamin D3 Reverses the Hippocampal Cytoskeleton Imbalance But Not Memory Deficits Caused by Ovariectomy in Adult Wistar Rats - Cassiana Siebert; Paula Pierozan; Janaina Kolling; Tiago Marcon dos Santos; Matheus Coimbra Sebotaio; Eduardo Peil Marques; Helena Biasibetti; Aline Longoni; Fernanda Ferreira; Regina Pessoa-Pureur; Carlos Alexandre Netto; Angela T. S. Wyse (NeuroMolecular Medicine, 2017)

D-Galactose Causes Motor Coordination Impairment, and Histological and Biochemical Changes in the Cerebellum of Rats - André Felipe Rodrigues; Helena Biasibetti; Bruna Stela Zanotto; Eduardo Farias Sanches; Felipe Schmitz; Vinícius Tejada Nunes; Paula Pierozan; Vanusa Manfredini; Débora Delwing Dal Magro; Carlos Alexandre Netto; Angela T.S. Wyse (Molecular Neurobiology, 2017)

Physical and chemical characteristics of water from the hydrographic basin of the Poxim River, Sergipe State, Brazil - Antenor Oliveira de Aguiar Netto; Carlos Alexandre Borges Garcia; José do Patrocínio Hora Alves; Robério Anastácio Ferreira; Marinoé Gonzaga da Silva (Environmental Monitoring and Assessment, 2013)

Chronic methylphenidate administration alters antioxidant defenses and butyrylcholinesterase activity in blood of juvenile rats - Felipe Schmitz; Emilene Barros da Silva Scherer; Maira Jaqueline da Cunha; Aline Andrea da Cunha; Daniela Delwing Lima; Débora Delwing; Carlos Alexandre Netto; Angela Terezinha de Souza Wyse (Molecular and Cellular Biochemistry, 2012)

Behavioral and neurochemical effects of proline - Angela T. S. Wyse; Carlos Alexandre Netto (Metabolic Brain Disease, 2011)

Sulfite increases lipoperoxidation and decreases the activity of catalase in brain of rats - Fábria Chiarani; Caren S. Bavaresco; Carlos S. Dutra-Filho; Carlos Alexandre Netto; Angela T. S. Wyse (Metabolic Brain Disease, 2008)

Intrastriatal Hypoxanthine Reduces Na+,K+-ATPase Activity and Induces Oxidative Stress in the Rats - Caren Serra Bavaresco; Fabria Chiarani; Clovis Milton Duval Wannmacher; Carlos Alexandre Netto; Angela Terezinha de Souza Wyse (Metabolic Brain Disease, 2007)

Intrastriatal injection of hypoxanthine reduces striatal serotonin content and impairs spatial memory performance in rats - Caren Serra Bavaresco; Fabria Chiarani; Eduardo Duringon; Marcelo Machado Ferro; Cláudio Da Cunha; Carlos Alexandre Netto; Angela Terezinha de Souza Wyse (Metabolic Brain Disease, 2007)

Homocysteine increases neuronal damage in hippocampal slices receiving oxygen and glucose deprivation - Bárbara Tagliari; Lauren L. Zamin; Christianne G. Salbego; Carlos Alexandre Netto; Angela T. S. Wyse (Metabolic Brain Disease, 2006)

Chronic Hyperprolinemia Provokes a Memory Deficit in the Morris Water Maze Task - Caren Serra Bavaresco; Emílio Luíz Streck; Carlos Alexandre Netto; Angela Terezinha Souza de Wyse (Metabolic Brain Disease, 2005)